PERFORMANCE AND MOLECULAR ANALYSIS OF POTATO LINES DEVELOPED FROM GAMMA RAYS AND EMS APPLICATIONS - & Abdulrasool, Annon (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
An experiment was conducted in a greenhouse - research station B - College of Agricultural Engineering Sciences, University of Baghdad, during the fall season of 2018 with the aim of propagating and initially studying the field performance of 18 and 20 potential potato lines derived from Rivera and Arizona cv. after in vitro exposure of nodal segments to different dosages of gamma rays (0, 10, 20, and 30 Gray) and EMS (0, 10, 20, and 30 mM). Each control cultivar and their derived lines were independently cultured in plastic bags according to the RCBD, with three replications. The results showed that the highest plant height and number of leaves were obtained from Arizona derived lines which gave 60.11 cm and 25.30 leaves.plant-1 in lines 207 and 222, respectively when compared with their control that gave 38.11 cm and 13.67 leaves.plant-1, respectively. Minitubers diameter, weight, and plant yield were in its highest values in Arizona derived lines 551, 551, and 459 which gave 35.73 mm.minituber-1, 33.13 g. minituber-1, and 133.8 g.plant-1, respectively compared to their control that gave 25.35 mm.minituber, 16.8 g.minituber, and 78.57 g.plant-1, respectively. The resulted lines were analyzed at the molecular level utilizing the inter simple sequence repeats (ISSR) markers and revealed that lines 69, 10, 68, 102, and 7 were the much distanced from its derived Rivera cultivar and gave 40.7%, 37.1%, 36.8%, 33.3%, and 30.0%, respectively while lines 551, 261, 474, and 254 were the much genetically distanced from their derived cultivar Arizona with genetic distances of 24.1%, 22.6%, 18.8%, and 17.6%, respectively.